2008
DOI: 10.1186/1757-1626-1-426
|View full text |Cite
|
Sign up to set email alerts
|

Primary lymphoma of the head and neck: two case reports and review of the literature

Abstract: Background: The head and neck is the second most common region for the extra-nodal lymphomas after that of gastrointestinal tract. Approximately 2.5% of malignant lymphoma arises in the oral and para-oral region. In this paper we report two cases of early stage head and neck lymphoma which were managed successfully with chemotherapy and a review of the related literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 12 publications
(22 reference statements)
0
21
1
2
Order By: Relevance
“…A rituximab, cyclophosphamide, doxorubicin, vincristine and prednisone regimen is considered to be the standard treatment for patients with advanced diffuse large B-cell lymphoma. [7] The prognosis for primary prostatic lymphoma is uncertain, due to the rarity of the disease. It has been suggested that the prognosis of nodal lymphomas may be similar to that of extranodal lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…A rituximab, cyclophosphamide, doxorubicin, vincristine and prednisone regimen is considered to be the standard treatment for patients with advanced diffuse large B-cell lymphoma. [7] The prognosis for primary prostatic lymphoma is uncertain, due to the rarity of the disease. It has been suggested that the prognosis of nodal lymphomas may be similar to that of extranodal lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…DLBCL, follicular lymphoma, and Burkitt lymphoma), [16] and DLBCL and EBV+ NK/T-cell lymphomas of the nose, paranasal sinuses, and oropharynx (Table 27-5) [17]. Secondary spread of follicular lymphoma into the salivary glands from adjacent lymph nodes is also common.…”
Section: Lymphomas Of the Head And Neck And Thyroidmentioning
confidence: 99%
“…They mainly involve lymph nodes, spleen and other non-hemopoietic tissues, with painless enlargement of lymph nodes being the most common presenting symptom. However, an important feature of NHL which distinguishes it from Hodgkin's disease is that NHL can arise in an extranodal site, either as a primary or occult lesion [1] [2].…”
Section: Introductionmentioning
confidence: 99%
“…Most NHLs arise in lymph nodes or other lymphatic tissues such as the spleen, Waldeyer's ring and thymus [2]. Involvement of extranodal organs is a common finding after staging investigation, however, about 25% -40% of NHL patients present with a primary extranodal lymphoma, and common presenting sites include gastrointestinal tract, pharynx, thyroid, lung, central nervous system, orbit, salivary glands and skin [3] [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation